Ethical Practice in the Accounting Publishing Process: Contrasting Opinions of Authors and Editors - Borkowski, Susan C. (Journal of business ethics, 2000)
Academic accounting researchers often offer anecdotal evidence that the publishing process is rife with unfair and unethical practices, and similar contradictory evidence supports accounting journal editors' claims that the process is fair and ethical. This study compares the perceptions of accounting authors and editors on the ethicacy and frequency of specific author, editor and reviewer practices. Both authors and editors are in general agreement about the ethical nature of editors and author practices. However, there are significant differences between the groups regarding reviewer behavior, and regarding the frequency of occurrence of questionable author, editor and reviewer practices. Additionally, the majority of authors believe that codes of publishing ethics are needed, while editors do not. Women authors are significantly more supportive of such ethical codes when compared to their male counterparts.